Draft literary work by Éamonn Ceannt entitled "Canamhaint" [dialect] - Ceannt, Éamonn, 1881-1916
Refers to the dialects of Irish and the revival and standardisation of the Irish language.
Keywords: Irish language -- Revival; Ireland -- History -- 20th century